Just Managing? What it Means for the Families of Austerity Britain - O'Brien, Mark (Open Reports Series, 2017)
"The 'just about managing'. 'Hardworking families'. 'Alarm-clock Britain'. In recent years British political discourse has been filled with these slogans, as politicians claim to speak on behalf of families who are in work, but struggling to get by. This book allows us to hear from some of these families directly. At a time when the impact of austerity is more relevant than ever, Just Managing? cuts through the debates and sloganeering to give some of the real people behind the headlines and statistics a chance to tell their stories. It tracks the lives of thirty working families in Liverpool over one year, as they struggle to manage on incomes at or around the National Minimum Wage. Their accounts are placed within the economic and political context that has shaped their experiences and that of millions of other working families across the country. This book is required reading for anyone seeking to understand what life is like at the sharp end of 'austerity Britain'."